Elections for Amur People’s Assembly in 1921 - V. L. Zemlyanskiy (Научный диалог)
The features of the organization and conduct of elections to the Parliament of the Amur state establishment -the Amur People’s Assembly is considered. Based on archival data and materials of periodicals of Vladivostok the author has studied the process of elections to the Supreme representative authority of Primorye. Main attention is paid to the election procedure in towns and in rural areas of the Primorsk region under the control of S. D. Merkulov’s government. The research urgency is caused by falling of interest of Russians to the electoral campaigns to the State Duma of the Russian Federation and regional parliaments. The article shows that the elections were held in government-controlled areas (southern Primorye, Petropavlovsk) and in the zone of alienation of the Chinese Eastern railway. Voting without significant difficulties were held in the cities of Vladivostok and Nikol'sk-Ussuriisk, and also in the southern rural areas of Primorsky region. It is concluded that the main problems for elections for the Amur People’s Assembly was the absenteeism of the population of Primorye due to the discontent with the coup and the actions of the guerrillas, which prevented voting in rural areas. It is reported that pro-government candidates won in the elections, however, the opposition-minded parliamentarians occupied more than a third of the seats in Parliament.